Factors affecting consumer preferences: A study among UUM Kuala Lumpur campus students - Faidatui Syahirah, Ali Sabri (2021)
The increasing number of entrepreneurs shows a competitive competition in the Malaysia business market. It will help country to increase the economic growth and contribution by encouraging more local entrepreneur start a business. Malaysian government committed in developing more entrepreneurs through education, financial, and others support. However, the competition among International brand will give effect on local brand that offers variety of value and assumptions. Understanding consumer preferences is considered to be a key priority for business success. Therefore, determining the factors that affect consumer preference is an important. This paper was designed to examine the effects of brand, perceived quality, price and country of origin on consumer preferences towards international brands at Universiti Utara Malaysia, Kuala Lumpur Campus postgraduates. The total of 489 questionnaires has been distributed to 489 who are postgraduates students, however, only 218 questionnaires have been successfully collected for the data analysis. Study analysed by using Statistic Package for Social Science (SPSS) revealed that only two out of four variables having significant relationship with the consumer preference, which are brand and perceived quality. In addition, the recommendation and conclusion for the related parties and future research were also discussed.